2021
DOI: 10.1038/s42003-020-01589-7
|View full text |Cite
|
Sign up to set email alerts
|

A risk marker of tribasic hemagglutinin cleavage site in influenza A (H9N2) virus

Abstract: Low pathogenic avian influenza A(H9N2) virus is endemic worldwide and continually recruit internal genes to generate human-infecting H5N1, H5N6, H7N9, and H10N8 influenza variants. Here we show that hemagglutinin cleavage sites (HACS) of H9N2 viruses tended to mutate towards hydrophilic via evolutionary transition, and the tribasic HACS were found at high prevalence in Asia and the Middle East. Our finding suggested that the tribasic H9N2 viruses increased the viral replication, stability, pathogenicity and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Therefore, all subsequent analyses were performed on this stretch of 12 nucleotides/4 amino acids. As mentioned above, it has been shown that the number of As in the region immediately preceding the HA cleavage site is positively associated with acquisition of insertions [ 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. We therefore set out to compare the total number of As present in the P4 to P1 region of all sequences and their disposition into stretches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, all subsequent analyses were performed on this stretch of 12 nucleotides/4 amino acids. As mentioned above, it has been shown that the number of As in the region immediately preceding the HA cleavage site is positively associated with acquisition of insertions [ 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. We therefore set out to compare the total number of As present in the P4 to P1 region of all sequences and their disposition into stretches.…”
Section: Resultsmentioning
confidence: 99%
“…However, HAs of LPAIVs from other subtypes that have so far never evolved to HPAIVs present similar conserved structures (e.g., H6) [ 26 ], suggesting that the presence of a stem-loop is not sufficient for insertion generation at the HA cleavage site. It has also become clear that the nucleotide sequence of the region coding for the HA cleavage site has a strong impact on the generation of insertions, with sequences rich in adenines (A; cRNA orientation) and particularly with long stretches of As being insertion-prone [ 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Serial passaging experiments have revealed that insertions are more easily acquired in H5 and H7 viruses containing substitutions, leading to more A-rich R or K codons at the HA cleavage site than viruses having a consensus LPAIV motif [ 28 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, the H9N2 AIVs have become endemic in poultry in different countries, posing a huge economic loss to the poultry farming industry (8)(9)(10)(11)(12). Furthermore, H9N2 AIVs have conduced to some zoonotic events by providing the internal segments to reassortment viruses such as H7N9, H5N6, and H10N8 (13,14). Strikingly, it has been reported that H9N2 AIVs continuously cross the species barriers to infect mammalians, including dogs, pigs, and humans (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…However, LPAIVs have been shown to replicate in the oviducts and kidneys of some infected birds, suggesting the presence of proteases in other tissues that may be able to process monobasic cleavage sites [13][14][15]. Recent H9N2 isolates from Asia and Middle East have increasingly shown the presence of a tri-basic HA cleavage site, which was associated with increased pathogenicity and transmission in chickens in comparison with viruses with mono-basic cleavage sites [16]. However, these viruses with the tri-basic cleavage site did not demonstrate a HPAI phenotype but rather an intermediate step towards a gain in pathogenicity, and were still considered LPAIV.…”
Section: Introductionmentioning
confidence: 99%